1997
DOI: 10.1073/pnas.94.12.6380
|View full text |Cite
|
Sign up to set email alerts
|

High level expression of p27 kip1 and cyclin D1 in some human breast cancer cells: Inverse correlation between the expression of p27 kip1 and degree of malignancy in human breast and colorectal cancers

Abstract: The expression of cyclin-dependent kinase inhibitor p27 kip1 in human tumors and normal tissues was investigated using a panel of novel anti-p27 kip1 mAbs. An inverse correlation between expression of p27 kip1 and cell proliferation was generally observed after analyzing its expression in 25 different normal human tissues. In some highly proliferative human breast cancer cells, however, high level p27 kip1 expression was seen, indicating the existence of a mechanism by which some growing tumor cells may tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
256
3
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(286 citation statements)
references
References 21 publications
23
256
3
4
Order By: Relevance
“…Moreover, in the ER-positive subgroup of breast tumors, FXR expression was highly correlated with cyclin D and p27 protein expression. This result is in line with the fact that the expressions of both cyclin D1 and p27 are closely related [29,30] and correlate with estrogen receptor positivity in primary breast cancer [31,32]. Therefore, insofar as mitogen-dependent progression through G 1 phase is mediated by induction of the cyclin D family [33,34], our study suggests that FXR expression is associated with cell proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in the ER-positive subgroup of breast tumors, FXR expression was highly correlated with cyclin D and p27 protein expression. This result is in line with the fact that the expressions of both cyclin D1 and p27 are closely related [29,30] and correlate with estrogen receptor positivity in primary breast cancer [31,32]. Therefore, insofar as mitogen-dependent progression through G 1 phase is mediated by induction of the cyclin D family [33,34], our study suggests that FXR expression is associated with cell proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…We also found that ectopic overexpression of cyclin E in the mouse mammary HC11 cell is associated with increased expression of p27 . These ®ndings are not restricted to cell lines since there is a signi®cant correlation between high expression of cyclin D1 and p27 in primary human cancers of the colon (Ciaparrone et al, 1998;Fredersdorf et al, 1997), breast (Fredersdorf et al, 1997) and esophagus (Doki et al, personal communication). In the present study we found that ectopic overexpression of p27 was associated with increased expression of cyclin D1 (Figure 2b), suggesting the existence of a homeostatic feed back loop in the reverse direction.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high p27 expression is associated with low grade (well and moderately di erentiated) of carcinomas (Fredersdorf et al, 1997;Catzavelos et al, 1997;Ciaparrone et al, 1998;Singh et al, 1998), suggesting that p27 may play a role in the di erentiation of carcinoma cells. The present in vitro studies are consistent with these in vivo results since we found that increased expression of p27 in HT29 colon carcinoma cells only partially inhibited growth but markedly enhanced SB induced differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These comprised seven grade 2, 64 grade 3 and one pure DCIS of comedo type. In addition to the selection of these tumours on the basis of grade, it was possible to assess whether they were biologically representative of sporadic tumours of the designated grade on the basis of published data for expression of p27 Kip1 (Fredersdorf et al, 1997) and the oestrogen receptor. These analyses con®rmed that the control sporadic tumours were representative of their allocated grade.…”
Section: Tumoursmentioning
confidence: 99%